Prinsip Perencanaan Kearsipan terhadap Ketercapaian Akreditasi Madrasah - Safiudin, Safiudin; Syarifudin, Encep; Muslihah, Eneng; Masfuah, Syifa (Al-Liqo: Jurnal Pendidikan Islam, 2024)
Archives are an important component of preparing for madrasah accreditation. The research used qualitative methods with a case study approach at MTs Malnu Menes, Pandeglang Regency. Data collection is through observation, documentation and literature study, while the data analysis technique is triangulation. Research shows that archival planning principles that meet the criteria for madrasa accreditation include staff, finances, equipment, storage systems and selection of organizational systems. The archival planning must meet the elements of completeness, cost, flexibility, quality, relevance, retention, timeliness and variability. The archival planning is prepared by madrasah accreditation by preparing incoming and outgoing letters, archival retention schedules and providing archival facilities. Archive storage planning considers classification, storage, maintenance, records and natural factors. Planning an archival storage system includes checking, sorting, indexing, signaling, labeling, archival books and storage. Planning room archive facilities, cupboards, letter receiving equipment, letter storage equipment and correspondence equipment. Planning for archivists with competencies, namely general knowledge, organizational knowledge, archival knowledge, skills, accuracy, neatness and intelligence.